HaKI dan Masyarakat Lokal Indonesia - Sardjono, Agus (UI Scholars Hub, 2004)
There are several substansial problems remain on intellectual property rights in the local society of Indonesia. The needed for protection of intellectual property did not come from the civil society itself but from the pressure of external factor. Intellectual Property Regime is also known as capitalistic regime and that is the problem. The protection is given to the one who own the right, not for the real author. The characteristic of intellectual property is to protect individually. In the other hand, the background of local society of Indonesia, which consists of many tribes, lived based on communalistic. The opposite of concept did not avoid Indonesia for taking a step into ratification of international instruments of intellectual property rights protection. The reason behind is the position of Indonesia as a developing country which has powerless bargaining position put side by side with developed countries. This article attempts to offer another point of view to find out what is the real matter, the root of the problems, why intellectual property regime can not be implemented well in Indonesia.